Analysis of the Possibility of Earthquakes in the Tashkent Region - Abdunabiev, T. A.; Kurbanbaev, Sh. E. (European Journal of Life Safety and Stability (2660-9630), 2022)
The article analyzes the possible earthquakes in the territory of the Tashkent region. At the same time, information about the geographic location of the Tashkent region, land area, mountainous regions and weather is provided. Also touched upon the cities and districts of the region, as well as the population. It is noted that in the event of a strong earthquake on the territory of the region, it is possible to cause disruption of the facilities of living quarters, economy and communal areas of the population, as well as to lead to a disruption of the stability of the epidemiological situation.